A meta-analysis of the variables related to turnover intention among IT personnel - Özkan, Ahmet Hakan (Kybernetes, 2022)
PurposeThis study aims to investigate the relationships between job satisfaction, organizational commitment and turnover intention of information technology (IT) personnel.Design/methodology/approach3,844 studies which are published between 1998 and 2019 are screened on ScienceDirect, Scopus and ProQuest databases. 10,523 subjects formed the first data set regarding the relationship between job satisfaction and turnover intention, 7,903 subjects formed the second data set regarding the relationship between organizational commitment and turnover intention, 843 subjects formed the third data set regarding the relationship between empowerment and turnover intention, and 3,430 subjects formed the fourth data set regarding the relationship between job satisfaction and organizational commitment.FindingsResults showed that the effect size of the relationship between job satisfaction and organizational commitment is the strongest (r = 0.59). The effect size of the relationship between job satisfaction and turnover intention (r = −0.50), and the effect size of the relationship between organizational commitment and turnover intention r = −0.51) were also large. But the effect size of the relationship between empowerment and turnover intention was medium (r = −0.34).Originality/valueThis study is rare, and it can be used by the managers working in the IT industry.